Automated Microfluidic Platform for High‐Throughput Biosensor Development - Shitanshu Devrani; Daniel Tietze; Alesia A. Tietze (Advanced Sensor Research)
Abstract Biorecognition elements immobilized into nanopores have transformed point‐of‐care (POC) diagnostics by converting molecular interactions into electrical and fluorescent signals.This study introduces Bio‐Sensei, a high‐throughput screening (HTS) microfluidic platform based on nanopore biosensing. Integrating a robotic sampler, electrochemical, and fluorescence setup, Bio‐Sensei operates as an Internet of Things (IoT) platform with integrated data analysis. The platform's utility is demonstrated on functionalized with an amino terminal Cu(II)‐ and Ni(II)‐binding (ATCUN) peptide ion track‐etched membrane. Automated testing achieves a significantly higher F‐stat value than the critical threshold, while unsupervised clustering reveals optimal nanopores pore size. The biosensor demonstrates remarkable stability, selectivity, and sensitivity with detection limits of 10−6 using fluorescence and 10−15 M using cyclic voltammetry measurements. Combining these methods enhances machine learning models for Cu2+ concentration prediction, achieving receiver operating characteristic area under the curve values exceeding 95%.